2020
DOI: 10.1016/j.jdent.2020.103402
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of mineral loss as a function of depth using confocal laser scanning microscopy to study erosive lesions in enamel: A novel non-destructive image processing model

Abstract: Objective: The aim was to develop a novel image processing protocol for confocal laser scanning microscopy (CLSM) to study mineral distribution within erosive lesions as a function of depth. Methods: Polished bovine enamel samples (n=80) were divided into groups (8/group) with similar mean surface microhardness (SMH) values. Samples underwent erosion (1% citric acid pH3.8) for 1,5,10,15, or 30min, with or without stirring giving 10 treatment groups in a 2*5 factorial design. SMH was used to measure erosive sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Additionally, Hookham et al 2020 demonstrated that calcium/phosphate loss following acid attack (1% citric acid) on bovine enamel resulted in deeper penetration of rhodamine B dye and thus an increase in fluorescence volume measuring using confocal laser scanning microscopy. Their study showed that as erosion lesion depth increased, so did the fluorescent volume detected due to the deeper penetration of rhodamine B dye into the eroded enamel [41]. However, whilst their study used polished bovine enamel, the principle outcome they demonstrated could potentially translate to the human enamel model; though this would require future study.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Hookham et al 2020 demonstrated that calcium/phosphate loss following acid attack (1% citric acid) on bovine enamel resulted in deeper penetration of rhodamine B dye and thus an increase in fluorescence volume measuring using confocal laser scanning microscopy. Their study showed that as erosion lesion depth increased, so did the fluorescent volume detected due to the deeper penetration of rhodamine B dye into the eroded enamel [41]. However, whilst their study used polished bovine enamel, the principle outcome they demonstrated could potentially translate to the human enamel model; though this would require future study.…”
Section: Discussionmentioning
confidence: 98%
“…30 Furthermore, the stereomicroscope was chosen to analyze the failure pattern because it allows for the acquisition of high-resolution images and enables the measurement of gaps in the four quadrants of the adhesive interface. 31 Finally, laser confocal microscopy was planned to evaluate the extent of resin tags because it is a non-destructive technique 32 that provides better visualization of the interaction between the dentin surface and the SU adhesive through the fluorescence of Rhodamine B present in the material.…”
Section: Discussionmentioning
confidence: 99%
“…CLSM is a nondestructive technique that can quantify and visualize erosive lesions [ 70 ]. The technology combines laser scanning with the capture of traditional visible light microscope images to produce a detailed 3D image of the surface [ 51 ] ( Figure 4 ).…”
Section: Quantitative and Qualitative Evaluationmentioning
confidence: 99%